Model Inovasi Pengembangan Pemberdayaan Pemuda (Studi Kasus di Kabupaten Banyumas) - Dwiyanto Indiahono; Tobirin; Khayu Rohmi; Ranjani (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2026)
This study aims to develop a model for youth empowerment innovation in the context of rural development in Banyumas Regency, Central Java. The urgency of this study stems from the demographic fact that more than 52% of Indonesia’s population consists of Millennials and Gen Z, yet their participation in rural development is often hindered by limited access and a lack of a supportive ecosystem. As a strategic asset, the potential of young people needs to be harnessed through a model that integrates a multistakeholder approach, the use of digital technology, and the strengthening of socio-economic capital. This study employs a qualitative method using an in-depth case study approach. Data were collected through interviews with various stakeholders, field observations, and a comprehensive analysis of local policy documents. The main finding of this research reveals that institutional program fragmentation is the primary barrier to rural youth empowerment. To address this, the study proposes a 4-Pillar Model (capacity building, resource and capital access, a tech-based innovation ecosystem, and governance participation) driven by Pentahelix synergy and digital infrastructure to bridge the urban-rural divide. Implementing this strategic model is crucial to transforming rural youth into drivers of the local economy and achieving selfreliant, sustainable village development.